Diagnostic Value of Multimodal Intraoperative Neuromonitoring by Combining Somatosensory-With Motor-Evoked Potential in Posterior Decompression Surgery for Thoracic Spinal Stenosis - Liu, Tun; Yan, Liang; Qi, Huaguang; Luo, Zhenguo; Liu, Xuemei; Yuan, Tao; Dong, Buhuai; Zhao, Yuanting; Zhao, Songchuan; Li, Houkun; Liu, Zhian; Wu, Xucai; et al. (Frontiers in Neuroscience, 2022)
Background: Intraoperative neuromonitoring (IONM) has become an increasingly essential technique in spinal surgery. However, data on the diagnostic value of IONM in predicting impending postoperative neurological deficits (PONDs) for patients who underwent posterior decompression surgery for thoracic spinal stenosis (TSS) is limited. Furthermore, patients who are at the highest risk of waveform changes during the surgery remain unknown. Our purpose was to 1) assess the diagnostic accuracy of IONM by combining somatosensory- with motor- evoked potential (SSEP, MEP) in predicting PONDs for patients who underwent the surgery; 2) identify the independent risk factors correlated with IONM changes in our study population. Methods: A total of 326 consecutive patients who underwent the surgery was identified and analyzed. We collected the following data: 1) demographic and clinical data; 2) IONM data; 3) outcome data: details of PONDs, and recovery status (complete, partial, or no recovery) at the 12-month follow-up visit. Results: In total, 27 patients developed PONDs. However, 15, 6, and 6 patients achieved complete recovery, partial recovery, and no recovery, respectively, at the 12-month follow-up. SSEP or MEP change monitoring yielded better diagnostic efficacy in predicting PONDs as indicated by the increased sensitivity (96.30%) and AUC value (0.91). Only one neurological deficit occurred without waveform changes. On multiple logistic regression analysis, the independent risk factors associated with waveform changes were as follows: preoperative moderate or severe neurological deficits (p＝0.002), operating in the upper or middle thoracic spinal level (p＝0.003), estimated blood loss (EBL)≥400ml (p＜0.001), duration of symptoms ≥3 months (p＜0.001), and impairment of gait (p＝0.001). Conclusions: SSEP or MEP change is a highly sensitive and moderately specific indicator for predicting PONDs in posterior decompression surgery for TSS. The independent risks for IONM change were as follows: operated in upper- or middle- thoracic spinal level, presented with gait impairment, had massive blood loss, moderate or severe neurological deficits preoperatively, and had a longer duration of symptoms. Clinical Trial Registration: ChineseClinicalTrialRegistry.cn; Identifier: ChiCTR 2000032155. Level of Evidence: Level III, observational studies.